2022
DOI: 10.1007/s00441-022-03624-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of skin wound healing in non-diabetic and diabetic mice in excision and pressure experimental wounds

Abstract: Experimental models for chronic skin lesions are excision and pressure ulcer, defined as “open” and “closed” lesions, respectively, only the latter characterized by tissue hypoxia. Moreover, systemic diseases, such as diabetes mellitus, affect wound repair. Thus, models for testing new therapies should be carefully selected according to the expected targets. In this study, we present an extensive and comparative histological, immunohistochemical, and molecular characterization of these two lesions in diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…S. aureus is the most common pathogenic species in chronic wounds [ 50 , 51 ]. It has been reported that a full-thickness skin excision wound on a rodent, for example mouse, is very clinically relevant [ 52 , 53 ]. Therefore, to further assess the antibacterial effect and therapeutic efficacy of the designed MN patches in promoting wound healing, we established a full-thickness skin wound model (diameter: 1 cm) with S. aureus infection on the backs of mice.…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus is the most common pathogenic species in chronic wounds [ 50 , 51 ]. It has been reported that a full-thickness skin excision wound on a rodent, for example mouse, is very clinically relevant [ 52 , 53 ]. Therefore, to further assess the antibacterial effect and therapeutic efficacy of the designed MN patches in promoting wound healing, we established a full-thickness skin wound model (diameter: 1 cm) with S. aureus infection on the backs of mice.…”
Section: Resultsmentioning
confidence: 99%
“…PLLA loaded with 15% GM18 (PLLA15GM18) was chosen, based on the results of the GM18 release tests and from previous in vitro studies on mesenchymal stem cells . This experiment was conducted in the pressure ulcer model in diabetic mice, as already established and characterized in our lab. , Photos of representative ulcers from the three experimental groups at 14 days from the first medication are shown in Figure A. The repaired area was measured as % value on day 14 compared to day 3 (when surgical curettage and the first medication were performed) and expressed as “residual wound area”.…”
Section: Resultsmentioning
confidence: 99%
“…For this in vivo study, we used a model of skin wound currently used by researchers to mimic chronic, nonhealing wounds, consisting of a pressure ulcer in db/db mice, a widely used mouse model of type 2 diabetes mellitus . These mice develop progressive sensory loss, electrophysiological impairments, and skin innervation loss: the skin repair process is also much slower in db/db than in control mice, making this mouse model highly appropriate for testing pro-healing compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We accomplished this by studying not only vascularization but also collagen deposition. We used Day 14 and Day 35 to represent time points within the proliferation and remodeling phases, respectively (Baldassarro et al, 2022). In a previous study, DS-SILY was shown to decrease collagen degradation by inhibiting MMP, thus, reducing dermal scarring (Stuart et al, 2011).…”
Section: Discussionmentioning
confidence: 99%